APLIKASI PUPUK ANORGANIK DAN ORGANIK HAYATI PADA BUDIDAYA PADI SRI (System of Rice Intensification) - Muchlis Muhammad Bakrie; Iswandi Anas; Sugiyanta Sugiyanta; Komaruddin Idris (Jurnal Ilmu Tanah dan Lingkungan, 2010)
Excessive use of inorganic fertilizers mainly NPK causes soil degradation, environment pollution, decreases production, and reduces soil biological activity. System of rice intensification is one method of rice cultivation. SRI main principles are seed transplanting at young age (7-11 days old), transplanting use single seedling methode, seedlings at wide plant spacing ≥ 25x25 cm, intermittent irrigation and field conditions are not flooded, and reduction of chemical fertilizers and application of organic fertilizer. This research was conducted at Situgede Village, West Bogor District, Bogor. The research design was split plot randomized complete block design with three blocks. Two rice cultivation system as the main plot and five combinations of fertilizer application as sub plot. In the main plot consisted of two rice cultivation which is conventional and SRI while the subplot consisted of five combinations of fertilizer application is no fertilition, 100% inorganic fertilizers (Urea = 250 kg ha-1, SP-36 = 75 kg ha-1 and KCl = 50 kg ha-1), 75% inorganic fertilizers (Urea = 187 kg ha-1, SP-36 = 56.8 kg ha-1 and KCl = 37.5 kg ha-1) + 200 kg of bio-organicfertilizer, 50% inorganic fertilizers (Urea = 125 kg ha-1, SP-36 = 37.5 kg ha-1 and KCl = 25 kg ha-1) + 200 kg of bio-organicfertilizer and 50% inorganic fertilizers (Urea = 125 kg ha-1, SP-36 = 37.5 kg ha-1 and KCl = 25 kg ha-1). The results showed that SRI method produced maximum number of tillers higher that of 25.8 tillers/hill or an increase of 64.33% compared with conventional methods. Wet and dry shoot weight of wet and dry weight of root is greater in successive SRI method of 13.3%, 19.1%, 1.40% and 41.8% compared with the conventional method. The number of productive tillers, grain number/panicle, 1000 grains weight, root wet weight and dry grain at SRI method was higher than those in conventional method respectively 58.6%, 37.0%, 2.50%, 25.1% and 32.6%. The uptake of N and P in the SRI method higher at 72.0% and 100% compared to conventional method. Application 50% inorganic fertilizer + 200 kg bio-organic fertilizer, producing more fresh weight biomass, plant dry weight, wet weight and dry weight, number of productive tillers, 1000 grain weight respectively 13.9%, 42.0%, 49.8%, 74.0%, 10.7% and 2.48% compared with the dosage recommendations dose or 100% inorganic fertilizer. N, P and K uptake at 50% inorganic fertilizer + 200 kg of bio-organic fertilizer treatment higher (55.6%, 66.7% and 46.2%) than the full recommendation dose of inorganic fertilizer. Bio-organic fertilizer can be used as substitute of NPK fertilizer.Keywords : Bio-organic fertilizer, inorganic fertilizer, System of Rice Intensification (SRI)